STUDI KESESUAIAN PERENCANAAN TANAMAN KARET DI WILAYAH KESATUAN PENGELOLAAN HUTAN PRODUKSI MODEL DAMPELAS-TINOMBO DESA SILUTUNG KECAMATAN TINOMBO SELATAN KABUPATEN PARIGI MOUTONG - Istiani, Trisna Ayu; Hamzari, Hamzari; Arianingsih, Ida (Universitas Tadulako, 2016)
The Model of Production Forest Management Unity of Dampelas – Tinombo has arranged a plan to develop rubber plant forest in its area, then put in the document to be the development plant of rubber in the Model of Production Forest Management Unity of Dampelas – Tinombo, Silutung village South Tinombo subdistrict by placing the society as the main actors in the implementation. The research was conducted for three months that began on April up to the month of Juli 2015. The research location was in the Production Forest in the Model of Production Forest Management Unity of Dampelas – Tinombo. The instrument applied in the research was questionnaire that used as primary data instrument in the location and technical design 2014 of The Production Forest Management Unity of Dampelas – Tinombo. The resarch method applied was survey method. The method that used to observe the actual condition of the location by deep interview method with 43 persons of respondents. The aim of the research was to find out the comformity of the development plan of rubber in the Model of Production Forest Management Unity of Dampelas – Tinombo with the actual condidtion in the location. The analysis that used were descriptive and comparison analysis. The result of the research showed that the comformity between technical design of the forest rehabilitation and land with recent condition in the location were seedling activities (100%), planting activities (100%), preserving activities (100%), protecting and saving activities (100%), seed needing activities and seeds supplying alternative (100%), activities of materials and means needs (88,8%), group organization activities (100%), technical guiding activities (100%). But there were three activities that had not maximal realized, they were the activities of supporting infrastructure (37,2%), the activities of elucidation and assistance (0%) and also training activities (0%).Keywords :Comformity, Rubber Plant, Forest Management Unity, Silutung village.